Epistemología Y Educación: (Breve Trazo) de Platón a Hegel - Espinosa Proa, Sergio (Boletim Técnico do Senac, 2006)
This essay defends the idea that education and epistemology are necessarily related. Since its origins, the “object” of philosophy is not absolutely an object – or a given collection of them – but the whole. To say that the task of philosophy is to refl ect on the whole – or being – will result in extreme shock, even more so for a modern mentality. Education is not mere knowledge transmission. To this extent, it does not require “an epistemology” to adequately fulfi ll such a task. On the contrary, all education occurs within an epistemology, within a metaphysics. That philosophy has been reduced to the size and rank of epistemology was the result of a prolonged process of weakening and decomposition.